2012
DOI: 10.7314/apjcp.2012.13.8.3653
|View full text |Cite
|
Sign up to set email alerts
|

Hyperin Extracted from Manchurian Rhododendron Leaf Induces Apoptosis in Human Endometrial Cancer Cells Through a Mitochondrial Pathway

Abstract: Background: A number of effective prevention measures have been introduced in attempts to substantially reduce both the incidence and mortality due to many kinds of cancer. The search for new anti-cancer compounds in foods or in plant medicines is one realistic and promising approach to prevention. Chinese medicines provide a rich pool of novel and efficacious agents for cancer prevention and treatment. Previously it was demonstratrated that hyperin extracted from the Manchurian rhododendron leaf reduces the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Hyperoside is a flavonol glycoside mainly found in plants of the genera Hypericum and Crataegus [29] . Pharmacological investigations have demonstrated that hyperoside has anti-oxidant [30] , anti-cancer [31] and anti-inflammatory activities [32][33][34] . This compound exerts anti-inflammatory effects by suppressing the production of proinflammatory cytokines through inhibiting the activation of the NF-κB signaling pathway in human endothelial cells [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperoside is a flavonol glycoside mainly found in plants of the genera Hypericum and Crataegus [29] . Pharmacological investigations have demonstrated that hyperoside has anti-oxidant [30] , anti-cancer [31] and anti-inflammatory activities [32][33][34] . This compound exerts anti-inflammatory effects by suppressing the production of proinflammatory cytokines through inhibiting the activation of the NF-κB signaling pathway in human endothelial cells [33] .…”
Section: Introductionmentioning
confidence: 99%
“…The 2008 World Health Organization (WHO) cancer report estimated that worldwide deaths are likely to rise to over 11 million in 2030; therefore, new, safe, and effective anticancer agents are needed (5). In recent years, the anticancer effects of synthetic chemicals and natural extracts of plants have gained prominence (9).…”
Section: Discussionmentioning
confidence: 99%
“…All these factors have led scientists to continue to develop alternative cancer treatment strategies (5). In this context, a number of synthetic compounds and natural products were evaluated for their efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin-3-O-β-D-galactopyranoside, also known as hyperoside, is a flavonol glycoside mainly found in plants of the genera Hypericum and Crataegus [20] . Previous studies have shown that hyperoside has anti-oxidant [21] , anticancer [22,23] and anti-inflammatory activities [24][25][26] . Furthermore, hyperoside produced anti-cancer effects through inducing apoptosis [22] and inhibiting of oncogenic microRNA-27a [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that hyperoside has anti-oxidant [21] , anticancer [22,23] and anti-inflammatory activities [24][25][26] . Furthermore, hyperoside produced anti-cancer effects through inducing apoptosis [22] and inhibiting of oncogenic microRNA-27a [27] . However, whether hyperoside induces autophagy, and the role it plays in cell death in human lung cancer cells, remain unclear.…”
Section: Introductionmentioning
confidence: 99%